Hop-on hop-off: importin-α-guided tours to the nucleus in innate immune signaling - Wirthmueller, Lennart; Roth, Charlotte; Banfield, Mark J.; Wiermer, Marcel (Frontiers in Plant Science, 2013)
Nuclear translocation of immune regulatory proteins and signal transducers is an essential process in animal and plant defense signaling against pathogenic microbes. Import of proteins containing a nuclear localization signal (NLS) into the nucleus is mediated by nuclear transport receptors (NTRs) termed importins, typically dimers of a cargo-binding alpha-subunit and a beta-subunit that mediates translocation through the nuclear pore complex (NPC). Here, we review recent reports of importin-alpha cargo specificity and mutant phenotypes in plant- and animal-microbe interactions. Using homology modeling of the NLS-binding cleft of nine predicted Arabidopsis alpha-importins and analyses of their gene expression patterns, we discuss functional redundancy and specialization within this transport receptor family. In addition, we consider how pathogen effector proteins that promote infection by manipulating host cell nuclear processes might compete with endogenous cargo proteins for nuclear uptake.